Localization of Enzymes of Ureide Biosynthesis in Peroxisomes and Microsomes of Nodules - Hanks, Joanna F. (1981)
The intracellular location of enzymes involved in the synthesis of the ureides, allantoin and allantoic acid, was investigated in nodules of Glycine max L. Merr. Cellular organelles were separated on isopycnic sucrose density gradients. Xanthine dehydrogenase activity (270 nanomoles per min per gram fresh weight) was totally soluble, whereas approximately 15% of the total uricase and catalase activities (1 and 2000 micromoles per minute per gram fresh weight, respectively) was in the fraction containing intact peroxisomes. Allantoinase activity (680 nanomoles per minute per gram fresh weight) was associated with the microsomal fraction, which apparently originates from the endoplasmic reticulum.